Developing a dashboard for program evaluation in competency-based training programs: A design-based research project - Yilmaz, Yusuf; Carey, Robert; Chan, Teresa M; Bandi, Venkat; Wang, Shisong; Woods, Robert A; Mondal, Debajyoti; Thoma, Brent (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: Canadian specialist residency training programs are implementing a form of competency-based medical education (CBME) that requires the assessment of entrustable professional activities (EPAs). Dashboards could be used to track the completion of EPAs to support program evaluation.Methods: Using a design-based research process, we identified program evaluation needs related to CBME assessments and designed a dashboard containing elements (data, analytics, and visualizations) meeting these needs. We interviewed leaders from the emergency medicine program and postgraduate medical education office at the University of Saskatchewan. Two investigators thematically analyzed interview transcripts to identify program evaluation needs that were audited by two additional investigators. Identified needs were described using quotes, analytics, and visualizations.Results: Between July 1, 2019 and April 6, 2021 we conducted 17 interviews with six participants (two program leaders and four institutional leaders). Four needs emerged as themes: tracking changes in overall assessment metrics, comparing metrics to the assessment plan, evaluating rotation performance, and engagement with the assessment metrics. We addressed these needs by presenting analytics and visualizations within a dashboard.Conclusions: We identified program evaluation needs related to EPA assessments and designed dashboard elements to meet them. This work will inform the development of other CBME assessment dashboards designed to support program evaluation.